Relatório do estágio de ensino da prática pedagógica supervisionada. O estudo e a produção de textos funcionais, privilegiando os textos instrucionais - Santos, Maria de Fátima (2015)
Over the three semesters, inserted in the Masters Degree for Teaching in Pre-school Education and Primary School, there were two internships, inserted in the discipline of Supervised Teaching Practice I, II and III. In the first two semesters the internship took place at Escola Básica do 1.º Ciclo com Jardim de Infância da Rua Jau, in Lisbon, in the context of Preschool Education. The group consisted of 22 children of both sexes, aged 3 to 5 years. The internship in the context of the 1st Cycle of Primary Education, held during the third quarter, was held at Escola Básica n.º 31 do Lumiar, in Lisbon. The class of 3rd and 4th year was composed of 26 elements. With this report I intend to introduce the institutions and groups with whom I met and describe and reflect on the work that I developed, together with the children. I also expose a problem that was related to the different levels of development of the group, due to the different ages that existed in the pre-school room. And finally, I present the project I prepared to implement with the class the Primary School.